Using the Leiden Rankings as a heuristics: Evidence from Italian universities in the European landscape - Cinzia Daraio; Simone Di Leo; Loet Leydesdorff (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
We propose an innovative use of the information provided by the Leiden Rankings (LR). Although LR only consider research output of major universities reported in Web of Science, statistical analysis of LRs combined with network mapping can reveal the complexity of research performance measurement. Yet, one can identify ''outlying'' institutions that perform significantly below or above expectations; these can be further analyzed using case studies. Outliers can inform and guide science policies about alternative options. Analyzing the case of the Politecnico di Bari, we observe that ''small teams'' led by young and promising scholars can push the performance of a university up to the top of the LR. Supporting ''emerging teams'', as argued by Moed (2017), can thus be an alternative to research support policies, adopted to encourage virtuous behaviors and best practices in research.
Keywords: I23; Z18; 330; University rankings; Leiden Rankings; Italian universities; best research practices; Politecnico di Bari; case study; emerging groups